Comparison of mutation spectrum, hemoglobin profiles and hematological features between transfusion dependent and non-dependent patients of Hb E/β Thalassemia - Islam, Maliha (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.